PENYULUHAN TENTANG MANAJEMEN HASIL INDUSTRI RUMAHAN DI UD.DUA PUTRI DALAM RANGKA UNTUK MENINGKATKAN DAN MEMBERDAYAKAN POTENSI WILAYAH - Hidayat, Taufik; Pohan, Muhammad Munawir; Tiara, Tiara (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Nowadays, there are many alternatives that can be used to turn into business opportunities, for example in the trade sector there are many things that can be done to expand the scope of the business and develop the business being undertaken, for example using technology to reach more consumers and connections. It can also be done by empowering existing regional potential. This research aims to increase and empower regional and business potential at the Dua Dutri Trading Business (UD) in Bakir village. The research method used in this research is qualitative with the approach used, namely socialization. The data sources in this research were obtained through observations, interviews and documentation. The data in this research was processed using qualitative analysis, where the data obtained was presented in descriptive analysis. The results of this research show that business owners have full responsibility for their company employees and business owners are starting to reconsider and examine more deeply the potential of their region and business owners also agree with the suggestions and input that the author has put forward such as utilizing regional potential, connections. trade, and alternative sales during counseling/socialization.